2018
DOI: 10.19082/6279
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effect of riboflavin on pediatric migraine: a randomized, double-blind, placebo-controlled trial

Abstract: Background and aimRiboflavin may have an acceptable effect on migraine among children. This study was carried out to determine the prophylactic effect of riboflavin on migraine in children.MethodsThis randomized clinical trial study was performed at Shahid Beheshti Hospital in Kashan, Iran from December 2012 to February 2015. Ninety children with migraine were allocated randomly into 3 groups (placebo, low-dose and high-dose riboflavin). The outcomes (frequency, intensity and duration of headaches) were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Two previous systematic reviews that evaluated the role of riboflavin in the prevention of migraine assessed the same studies (three RCTs and one retrospective study) [ 20 , 21 ]. Among these studies, two—one RCT and one retrospective study—reported that riboflavin was effective [ 22 , 23 ], while the other two reported ineffectiveness [ 24 , 25 ]. The latter two studies concluded that there was a lack of evidence to support the use of riboflavin for pediatric migraine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two previous systematic reviews that evaluated the role of riboflavin in the prevention of migraine assessed the same studies (three RCTs and one retrospective study) [ 20 , 21 ]. Among these studies, two—one RCT and one retrospective study—reported that riboflavin was effective [ 22 , 23 ], while the other two reported ineffectiveness [ 24 , 25 ]. The latter two studies concluded that there was a lack of evidence to support the use of riboflavin for pediatric migraine.…”
Section: Resultsmentioning
confidence: 99%
“…The latter two studies concluded that there was a lack of evidence to support the use of riboflavin for pediatric migraine. However, the former two positive studies have recently been published [ 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 28 On this review, we limited the participants to adult population because there was limited number of studies done in paediatric population and a few of the studies done involved other supplements such as riboflavin in paediatric population. 29 All the included studies had small number of participants and this limit the applicability of CoQ10 thus the larger samples size is needed for a better result. The information on adverse events came from only one trial which are diarrhoea and chromaturia.…”
Section: Discussionmentioning
confidence: 99%
“…Seven previous studies, including four RCTs, evaluated riboflavin’s role in preventing pediatric migraines ( Table 1 ). All studies except for two RCTs reported that riboflavin was effective [ 89 , 90 , 91 , 92 ]; the other two studies lacked evidence to support the use of riboflavin for pediatric migraines [ 93 , 94 ]. The following factors reportedly inhibit the effects of riboflavin: the presence of comorbid headaches, male sex, and age under 12 years [ 91 , 95 ].…”
Section: Clinical Evidence Of Riboflavin Efficacymentioning
confidence: 99%